PENGARUH VARIABEL MAKRO EKONOMI DAN HARGA MINYAK DUNIA TERHADAP INDUSTRI HALAL - Ali Mahdy Arrosikh; Ilmiawan Auwalin (Universitas Airlangga, 2019)
This paper aims to discover the influence of inflation rate, exchange rate, global’s oil price and FDI toward halal industry in 48 OIC’s member Countries. This research uses data by Statistical, Economic and Social Research and Training Centre for Islamic Countries (Sesric), world bank and Thomas Reuters with quantative approach and were analyzed by using panel data analysis. According to the result it is have positive significant influence to the halal industry in 48 OIC Countries. Inflation rate have a significant positive influant; exchange rate have a non significant positive influant; global’s oil price have a significant negative influant; and FDI have a non-significant negative influant toward the increasing of the unemployment rate in 48 OIC’s Countries.Keywords: Halal Industry, Inflation, Exchange Rate, Global’s Oil Price, FDIREFFERENCESAbdullah, Boedi, & Saebani, Beni Ahmad. 2014. Metode Penelitian Ekonomi Islam. Bandung: Pustaka Setia.Arsyad, Lincolin. 2010. Ekonomi Pembangunan. Yogyakarta: UPP STIM YKPN.Aziz, Yuhanis Abdul & Nyen Yui Chok. 2012.